Bioinspired cyclization of in situ generated γ-indolyl β, γ-unsaturated α-keto esters via an oxidative enamine process: facile approaches to pyrano[2, 3-b]indoles. Issue 22 (24th September 2021) - Wang, Man; Xiang, Qirui; Si, Wen; Song, Ran; Yang, Daoshan; Li, Ming; Lv, Jian
Abstract : A bioinspired cyclization of in situ generated γ-indolyl β, γ-unsaturated α-ketoesters with an oxoammonium salt via an oxidative enamine process has been developed. Abstract : A bioinspired cyclization of in situ generated γ-indolyl β, γ-unsaturated α-ketoesters with an oxoammonium salt via an oxidative enamine process has been developed. Under mild conditions, the reactions afforded pyrano[2, 3- b ]indoles, which are found in a wide range of bioactive compounds, in good yields (up to 86% yield).